Basel III and Algerian Banks _Field study a sample of Algerian Banks_ Bâle III et les banques algériennes _Etude sur le terrain d’un échantillon de banques algériennes_ - Bendehina, Meryem; Zirar, Soumia (Finance and Business Economies Review, 2019)
The objective of this study is to highlight the role of Bank of Algeria in establishing the basic pillars of Basel III and to identify the most important challenges facing the Algerian banking under this agreement by highlighting the content of Basel III, and to try of to identify actions taken the bank of Algeria in the context of the implementation of Basel.